WDR72 Mutations Associated with Amelogenesis Imperfecta and Acidosis. (May 2019) - Zhang, H.; Koruyucu, M.; Seymen, F.; Kasimoglu, Y.; Kim, J.-W.; Tinawi, S.; Zhang, C.; Jacquemont, M.L.; Vieira, A.R.; Simmer, J.P.; Hu, J.C.C.
Dental enamel malformations, or amelogenesis imperfecta (AI), can be isolated or syndromic. To improve the prospects of making a successful diagnosis by genetic testing, it is important that the full range of genes and mutations that cause AI be determined. Defects in WDR72 (WD repeat-containing protein 72; OMIM *613214) cause AI, type IIA3 (OMIM #613211), which follows an autosomal recessive pattern of inheritance. The defective enamel is normal in thickness, severely hypomineralized, orange-brown stained, and susceptible to attrition. We identified 6 families with biallelic WDR72 mutations by whole exome sequence analyses that perfectly segregated with the enamel phenotype. The novel mutations included 3 stop-gains [NM_182758.2: c.377G>A/p.(Trp126*), c.1801C>T/p.(Arg601*), c.2350A>T/p.(Arg784*)], a missense mutation [c.1265G>T/p.(Gly422Val)], and a 62, 138–base pair deletion (NG_017034.2: g.35441_97578del62138) that removed WDR72 coding exons 3 through 13. A previously reported WDR72 frameshift was also observed [c.1467_1468delAT/p.(Val491Aspfs*8)]. Three of the affected patients showed decreased serum pH, consistent with a diagnosis of renal tubular acidosis. Percentiles of stature and body weight varied among 8 affected individuals but did not show a consistent trend. These studies support that WDR72 mutations cause a syndromic form of AI and improve our ability to diagnose AI caused by WDR72 defects.